2011
DOI: 10.1111/j.1365-3156.2011.02923.x
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with focused antenatal care services: do health workers in rural Burkina Faso, Uganda and Tanzania perform all ANC procedures?

Abstract: Abstractobjective To assess health workers' compliance with the procedures set in the focused antenatal care (ANC) guidelines in rural Uganda, Tanzania and Burkina Faso; to compare the compliance within and among the three study sites; and to appraise the logistic and supply of the respective health facilities (HF).methods The cross-sectional study was conducted in the rural HF in three African countries. This descriptive observational study took place in HF in Nouna, Burkina Faso (5), Iganga, Uganda (6) and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 30 publications
10
59
0
Order By: Relevance
“…These findings are consistent with the findings by Conrad and others [35] whereby the different health education sessions did not take into consideration previous education topics, nor the mothers’ knowledge, leading to possible duplication and monotony of information [41]; further aggravated by the lack of individualised health education [35], also highlighted in our study.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with the findings by Conrad and others [35] whereby the different health education sessions did not take into consideration previous education topics, nor the mothers’ knowledge, leading to possible duplication and monotony of information [41]; further aggravated by the lack of individualised health education [35], also highlighted in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In Jimma, the coverage of laboratory testing during ANC was higher than the national coverage; thus, the issue of poor-quality laboratory facilities seems national. From other low-income countries, it is reported that the quality of ANC is compromised by shortages of laboratory reagents and drugs, low coverage of health education, and low compliance with the FANC guidelines and also that service varies between facilities and countries [912, 41, 4750]. In the present study, we found the same challenges and thus conclude that they seem to apply generally.…”
Section: Discussionsupporting
confidence: 78%
“…Generally, guidelines for FANC have not been fully implemented in low-income settings [8], and the quality of ANC is often low [912]. The ANC is increasingly focused on and acknowledged for providing health education, instructions on danger signs during pregnancy, and birth preparedness, as this is considered to be lifesaving and to reduce delay in seeking help [8].…”
Section: Introductionmentioning
confidence: 99%
“…At the time of this study, ANC service visit were only 60% in the country and few delivery at the health centre and hospital left the other with home delivery end up by delivery complications, as part of the Tanzania government strategies to promote the important of ANC visit is needed in order to overcome with this burden [21]. This could partly explain the high level of unawareness the important of ANC services.…”
Section: Discussionmentioning
confidence: 93%